Sosialisasi Protokol Kesehatan di masa Pandemi melalui Aktifitas Mewarnai Damar Kurung pada Anak Usia Dini - Riyadlotus Sholichah; Nur Rachmadani Fadhilah (Atthiflah: Journal of Early Childhood Islamic Education, 2021)
During a pandemic, the socialization of health protocols to children is important and needs to be researched. Child health protocol education needs serious attention. Not all the socialization of health protocols to children is able to present and frame health protocol material through an activity that is interesting, fun and in accordance with the characteristics of the child. An activity that is close to the child's daily life is play. This paper aims to describe the results of research on the importance of socializing early childhood health protocols through coloring Damar brackets. Damar brackets are a local cultural product of Gresik, East Java in the form of cube lanterns. The four sides are made of paper decorated with pictures / paintings, telling a familiar, cheerful and interesting daily life. In this study, the painting on the side of the resin brackets was substituted with the Health protocol image. The method in this research is descriptive qualitative. So this article describes how to socialize the Health protocol in early childhood through Damar Kurung coloring activities.